Pengaruh Pengendalian Intern, Tata Kelola Dan Gaya Kepemimpinan Terhadap Kinerja Pengelola Keuangan - Lisa Intan Sari; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to analyze 1) the effect of supervision on the tinancial management performance, 2) Obtain empirical approval of the requirements for managing financial governance, 3) the influence of leadership style on the performance of financial managers. In this study using Causality Design. The population in this study is the Regional Work Unit (SKPD) in Solok Regency which collects 27 SKPD. The population in this study was 27 SKPD. The method of analysis is multiple linear regression. The result of the study found 1) Control of apprenticeship in support of financial management in the Regional Work Unit of the Solok Regency, 2) Governance supports of financial management of the Solok District Work Unit, 3) Leadership style that supports financial management in the Regional Work Unit of Solok Regency, 4) Together the internal control variables, governance and leadership style are jointly agrees on the performance of financial managers in the Solok District Work Unit.